Зона особого внимания: роман / Сергей Алтынов - Алтынов Сергей Евгеньевич (Спецназ ВДВ, 2004)
Экземпляры: ф.13 (2004) / Инвентарный номер: 48358 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 52 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44